Economic policies in Spanish Morocco and the case of the electric cooperative: A venture for a nationalistic strategy - Federica Ferrero; Antonio M. Morone (The Journal of European Economic History (JEEH), 2021)
When the Treaty of Fez between the Makhzen (the Moroccan polity) and France was signed in 1912, Spain obtained its "Zone of influence" in northern Morocco. Like other European colonial powers, Spain resorted to using intermediaries to impose and strengthen its rule. In the city of Tetouan, the capital of the Spanish Zone, the administrative and political elite became the most suitable political intermediaries of the Spanish colonial administration. As an analytical and methodological category, intermediation reflects the subjectivity of the colonised in relation to the colonisers. This approach provides the framework for a historiographical interpretation focusing specifically on the political autonomy that colonial subjects obtained and enjoyed in the interstices of the colonial system. This paper deals with the case study of the Spanish-Moroccan Industrial (or Electric) Cooperative (Cooperativa Industrial Hispano-Marroquí), which was founded in 1928 in Tetouan thanks to Spanish, Jewish and Muslim shareholders. Given the broader framework of Spanish colonial economic policies in Morocco, the present study intends to demonstrate how the Cooperative acted as a financing instrument for al-Islah, the first Moroccan nationalist party, which was founded in Tetouan in 1936. The paper investigates the role that this economic venture played in developing the Moroccan nationalist movement and demonstrates that there was interplay between the economic and the political process of Morocco's transition to independence.
Keywords: 330